Honoring the Bios in Lutheran Bioethics - Meilaender, Gilbert (Dialog, 2004)
A Lutheran bioethic honors the body by being anti-Gnostic (and finding moral wisdom in the body's limits), by being anti-Pelagian (and requiring the reshaping of our disordered desires), and by being anti-Sadducean (in affirming that the new creation, though continuous with and fulfilling the old, also transforms and perfects it in ways that go beyond the earthly life we know). Such an approach to bioethics is illustrated here through discussion of the way in which new reproductive technologies may distort our understanding of the relation between the generations, thereby losing sight of the bios in bioethics.